(Ieee Ispass) Ieee International Symposium on Performance Analysis of Systems and Software 2011
DOI: 10.1109/ispass.2011.5762711
|View full text |Cite
|
Sign up to set email alerts
|

A semi-preemptive garbage collector for solid state drives

Abstract: Abstract-NAND flash memory is a preferred storage media for various platforms ranging from embedded systems to enterprise-scale systems. Flash devices do not have any mechanical moving parts and provide low-latency access. They also require less power compared to rotating media. Unlike hard disks, flash devices use out-of-update operations and they require a garbage collection (GC) process to reclaim invalid pages to create free blocks. This GC process is a major cause of performance degradation when running c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 26 publications
(18 reference statements)
2
14
0
Order By: Relevance
“…Because of its importance, extensive research has been reported in the literature to reduce the negative impact of GC in flash memory SSDs [14,20,34] and to cluster streaming data for data mining [2,7]. For a comprehensive review, readers are referred to [11,29,36].…”
Section: Related Workmentioning
confidence: 99%
“…Because of its importance, extensive research has been reported in the literature to reduce the negative impact of GC in flash memory SSDs [14,20,34] and to cluster streaming data for data mining [2,7]. For a comprehensive review, readers are referred to [11,29,36].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, some research introduced a GC selection algorithm designed for caching [28,12]. While reducing GC overhead for flash-based devices used in different applications has been previously discussed [20,18], there has been a lack of research on coordinating GC with different cache components.…”
Section: Related Workmentioning
confidence: 99%
“…We have used the Microsoft Research SSD simulator [4], which is based on DiskSim [8] and has been used in several other studies [25], [26], [44]. We have simulated a NAND flash SSD, with the parameters described in Table IV.…”
Section: B Simulator Implementation and Setupmentioning
confidence: 99%